A Prognostic Model for Development of Profound Shock among Children Presenting with Dengue Shock Syndrome. - Phung Khanh Lam; Dong Thi Hoai Tam; Nguyen Minh Dung; Nguyen Thi Hanh Tien; Nguyen Tan Thanh Kieu; Cameron Simmons; Jeremy Farrar; Bridget Wills; Marcel Wolbers (PLoS ONE)
Purpose To identify risk factors and develop a prediction model for the development of profound and recurrent shock amongst children presenting with dengue shock syndrome (DSS). Methods We analyzed data from a prospective cohort of children with DSS recruited at the Paediatric Intensive Care Unit of the Hospital for Tropical Disease in Ho Chi Minh City, Vietnam. The primary endpoint was "profound DSS", defined as ≥2 recurrent shock episodes (for subjects presenting in compensated shock), or ≥1 recurrent shock episodes (for subjects presenting initially with decompensated/hypotensive shock), and/or requirement for inotropic support. Recurrent shock was evaluated as a secondary endpoint. Risk factors were pre-defined clinical and laboratory variables collected at the time of presentation with shock. Prognostic model development was based on logistic regression and compared to several alternative approaches. Results The analysis population included 1207 children of whom 222 (18%) progressed to "profound DSS" and 433 (36%) had recurrent shock. Independent risk factors for both endpoints included younger age, earlier presentation, higher pulse rate, higher temperature, higher haematocrit and, for females, worse hemodynamic status at presentation. The final prognostic model for "profound DSS" showed acceptable discrimination (AUC=0.69 for internal validation) and calibration and is presented as a simple score-chart. Conclusions Several risk factors for development of profound or recurrent shock among children presenting with DSS were identified. The score-chart derived from the prognostic models should improve triage and management of children presenting with DSS in dengue-endemic areas.